PENGARUH BUDAYA ORGANISASI, KOMPETENSI DAN FASILITAS TERHADAP KEPUASAN PENGGUNA DI PUSAT PERPUSTAKAAN UNIVERSITAS ISLAM NEGERI (UIN) SYARIF HIDAYATULLAH - Ilyas Rikas Putra; Anwar Prabu Mangkunegara (Jurnal Satya Mandiri Manajemen dan Bisnis, 2022)
User satisfaction is an important topic because it can provide information that can be used by an organization to evaluate its final position. This study aims to determine the effect of organizational culture, competence and facilities on user satisfaction at the Syarif Hidayatullah State Islamic University (UIN) library center. The method used in this research is quantitative research using survey research methods. The quantitative research used in this study is associative in nature with the aim of knowing the relationship between two or more variables, so that it can explain and control a symptom. The results of this study can be interpreted that simultaneously organizational culture, content, and facilities have a significant effect on user satisfaction at the UIN Syarif Hidayatullah Library Center. Partially, organizational culture and facilities have a significant influence on user satisfaction at the Syarif Hidayatullah UIN Library Center, only competence partially has no effect on user satisfaction at the Syarif Hidayatullah UIN Library Center.